Graduates Performance: A Reflection of JPMC - Ojha, Arjun (Janaprakash Journal of Multidisciplinary Research, 2023)
Education is the act or process of imparting or acquiring general knowledge, developing the powers of reasoning and judgment of others intellectually. One of the major indicators for the development of nation is education. The first university of Nepal is Tribhuvan university established in 1959. Janaprakash Multiple Campus is community campus established in 2062 through affiliation from Tribhuvan university. Tracer study refers to the feedback survey or study of graduates/trainees to find out their actual position after completion of their academic/training course. Tracer study is a qualitative research design. Graduate batches 2016 to 2019 were selected for this study. Tracer team follow the questionnaire prescribed by UGC to conduct this study. Questionnaire were filled up through personal meet, email, telephone contact or by using social media. Collected information were enter into SPSS 25 version and prepare necessary table and calculation. Study was conducted mainly in four criteria those are profile of the graduates, employment status, situation of further study and response of graduates towards curriculum and facility offered by the institution. Most of the graduates were female from Kaski district and age of 22 to 26 years. Majority of graduates were unemployed and seeking for job. All of the graduates studied MBS in Tribhuvan university. Most of graduates were satisfied with facility and services provided by JPMC i.e., extra- curricular activities, problem solving ability, placement/attachment /internship, teaching learning environment, quality of education delivered, teachers and students relationship, library facility, sports facility, canteen and urinal facility but some were not satisfied with lab facility.